Investigation of the structural and charge properties of a polyamide nanofiltration membrane - Wallace, Edwin; Cuhorka, Jiří; Mikulášek, Petr (My University, 2017)
In this present work, a polyamide thin-film composite NF membrane (AFC 30) was used for characterization of the structural and charge surface properties. The structural properties are the pore radius (rp) and membrane thickness to porosity ratio (∆x/Ak) respectively. The interpretation of values from the different uncharged solutes rejection allows one to determine the structural properties of AFC 30. This was done by using modelling of rejection of the uncharged solutes with the aid of the Donnan steric partitioning model (DSPM). The fixed charge density on the membrane surface was determined by experiments with sodium chloride at different concentrations. The data from such a sodium chloride experiment(s) were used to calculate the effective charge density (ФX) by using the Spiegler–Kedem model together with a charge model called Teorell–Meyer–Sievers (TMS). Then, it has been revealed that the membrane charge depends solely on the salt concentration in the solution because of the ion adsorption onto the membrane surface.
Zjišťování strukturních parametrů a náboje polyamidové nanofiltrační membrány
Keywords: Nanofiltration; polyamide membrane; characterization; DSPM model; Spiegler-Kedem model; Nanofiltrace; polyamidová membrána; charakterizace; DSPM model; Spiegler-Kedemové model